A study of entrepreneurship subject (ETR 300) on UiTM Kedah students’ intention to start a business / Law Kuan Kheng ...[et al.] - Law, Kuan Kheng; Kor, Liew Kee; Khamis, Muhammad Sazri (2006)
The main purpose of the study is to investigate the impact of entrepreneurship education (ETR 300) on students’ inclination to start a business. We believe that a proper entrepreneurship education would be able to instill interest in the students to start a business. Therefore, a study was conducted to verify whether ETR 300 served its objective of providing the necessary knowledge and motivation for the UiTM Kedah students to start a business was felt to be timely. This is also in line with the government’s efforts to promote entrepreneurship as an alternative for our graduates to be self-employed rather than competing for a job in a tight labour market. The scope of the study was limited to students in UiTM Kedah taking the subject of ETR 300 consisting of 141 respondents. The research instrument drafted was named the Students’ Entrepreneurial Index, SEI which consists of 39 items that designed to tap into the three dimensions of entrepreneurship readiness: (a) Entrepreneurial Inclination; (b) Contextual Factors; and (c) Desirability of Control. The findings of this study suggested that the ETR 300 subject was able to enhance the entrepreneurial inclination among the students. Nevertheless, students’ high achievement grade in the final examination of ETR 300 subject had no significant relationship with their entrepreneurial inclination. The findings also revealed that gender did make a difference in their entrepreneurial inclination. Furthermore, it was found that the effect of previous exposure to entrepreneurship i.e. family business involvement contributed significantly to the difference in the mean score for SEI as well as its subscales. In conclusion, this study showed that ETR 300 was able to instill in the students their intention to start a business. It is suggested that the university should seriously look into the feasibility of making enterprise education compulsory to all students of UiTM to mould a greater number of students to be interested and enthusiastic to start their own business after graduation.